Sistem Informasi Berbasis Komputer : Peranan Data Warehouse, Software, Sistem Operasi Dan Programmer (Literature Review Executive Support Sistem For Business) - Fasya Saipullah; Habib Gustaf Maulana; Herdiansyah Ramzani; Indra Gunawan (Universitas Labuhanbatu, 2026)
The development of information technology in the digital era has encouraged organizations to transform towards data-driven and integrated decision-making systems. This study aims to comprehensively examine the role of data warehouses, software, operating systems, and programmers in the context of Executive Support Systems (ESS) as part of a computer-based information system (CBI). The method used is a systematic literature review of 15 scientific articles published between 2021 and 2025, obtained from scientific databases such as Google Scholar, Scopus, ScienceDirect, and indexed national journals. The analysis was conducted using a thematic synthesis approach to examine the contribution of each component to the effectiveness of ESS in supporting business decisions. The results of the study indicate that data warehouses play a central role in providing historical and integrated data as the basis for business intelligence and predictive analysis. Software and operating systems have been shown to determine the speed, security, and interoperability of the system, while programmers are a key factor in ensuring the sustainability of system development and adaptation to organizational needs. The integration of these four components results in an executive information system capable of improving operational efficiency, decision accuracy, and company competitiveness. Thus, this study provides a conceptual contribution to the development of more adaptive, intelligent, and sustainable computer-based information system models for the modern business world.